Prefrontal cortical distribution of muscarinic M2 and cannabinoid-1 (CB1) receptors in adult male mice with or without chronic adolescent exposure to Δ9-tetrahydrocannabinol. (12th February 2022) - Garzón, Miguel; Chan, June; Mackie, Ken; Pickel, Virginia M
Abstract: Chronic adolescent administration of marijuana's major psychoactive compound, ∆9-tetrahydrocannabinol (Δ9-THC), produces adaptive changes in adult social and cognitive functions sustained by prelimbic prefrontal cortex (PL-PFC). Memory and learning processes in PL-PFC neurons can be regulated through cholinergic muscarinic-2 receptors (M2R) and modulated by activation of cannabinoid-1 receptors (CB1Rs) targeted by Δ9-THC. Thus, chronic exposure to Δ9-THC during adolescence may alter the expression and/or distribution of M2Rs in PL-PFC neurons receiving CB1R terminals. We tested this hypothesis by using electron microscopic dual CB1R and M2R immunolabeling in adult C57BL/6 J male mice that had received vehicle or escalating dose of Δ9-THC through adolescence. In vehicle controls, CB1R immunolabeling was mainly localized to axonal profiles virtually devoid of M2R but often apposing M2R-immunoreactive dendrites and dendritic spines. The dendrites received inputs from CB1R-labeled or unlabeled terminals, whereas spines received asymmetric synapses exclusively from axon terminals lacking CB1Rs. Adolescent Δ9-THC significantly increased plasmalemmal M2R-immunogold density exclusively in large dendrites receiving input from CB1R-labeled terminals. In contrast, cytoplasmic M2R-immunogold density decreased in small spines of the Δ9-THC-treated adult mice. We conclude that Δ9-THC engagement of CB1Rs during adolescence increases M2R plasmalemmal accumulation in large proximal dendrites and decreases M2R cytoplasmic expression in small spines of PL-PFC.